2013
DOI: 10.1542/peds.2013-1021k
|View full text |Cite
|
Sign up to set email alerts
|

Limiting Home Visiting Effects: Maternal Depression as a Moderator of Child Maltreatment

Abstract: OBJECTIVE: To test, with a sample of adolescent mothers (16–20 at childbirth) and their first-born infants/toddlers (average age 1 year), whether the impact of a home visiting (HV) child maltreatment prevention program was moderated by maternal depression. METHODS: The study design was a randomized controlled trial of Healthy Families Massachusetts, a statewide child maltreatment prevention program. A total of 707 first-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 39 publications
(39 reference statements)
0
40
0
1
Order By: Relevance
“…We used a dummy variable to indicate whether each participant was randomly assigned to the program group or to the control group. See Easterbrooks et al (2013) for a discussion of home visiting effects on child maltreatment. In the current analysis, we include program participation as a control variable only, as program effects were not a focus of the current study.…”
Section: Methodsmentioning
confidence: 99%
“…We used a dummy variable to indicate whether each participant was randomly assigned to the program group or to the control group. See Easterbrooks et al (2013) for a discussion of home visiting effects on child maltreatment. In the current analysis, we include program participation as a control variable only, as program effects were not a focus of the current study.…”
Section: Methodsmentioning
confidence: 99%
“…First, current home-visiting programs have not been evaluated in low-resource special populations in the United States, including American Indian, new immigrant, and military families (2, 3)-populations that can be difficult to recruit and retain (3). Second, no home-visiting program currently endorsed by the Maternal, Infant, and Early Childhood Home Visiting Program (3,4) has been designed to target or shown reductions in both maternal drug use and mental health problems known to negatively affect children's early development (5)(6)(7)(8) and disproportionately affect mothers in at-risk settings. Third, current home-visiting interventions have not systematically measured intervention impact on children's emotional and behavior outcomes across early childhood (0 to 3 years) that are known to predict better developmental trajectories across the life course (9,10).…”
mentioning
confidence: 99%
“…For mothers in home visiting, improvement in depression is accompanied by changes in parenting stress and nurturing caregiving, both of which are key foci of home visiting programs. Treatments that are effective in reducing depression in this population, such as IH-CBT (Ammerman et al 2013a), can facilitate improvement and hold promise to prevent the negative consequences of depression that have been documented in home visiting (Duggan et al 2009; Easterbrooks et al 2013; McFarlane et al 2013). Mothers in home visiting exhibit most of the demographic and clinical factors that are associated with depression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, depression mitigates the positive effects of program participation (McFarlane et al 2013). Easterbrooks et al (2013) found that depressed mothers failed to receive the benefits of lowered rates of abuse and neglect relative to their non-depressed counterparts. An effective intervention for perinatal depression in this population holds potential to enhance the lives of low income mothers and children, improve developmental outcomes, and protect the sizable investment made in home visiting programs.…”
mentioning
confidence: 99%